REVIEW: Searching for the truth of book-length journalism - Bonita Mason (Asia Pacific Network, 2015)
Mason, Bonita. (2015). Searching for the truth of book-length journalism. Pacific Journalism Review, 21(2): 200-203. Review of Telling True Stories: Navigating the challenges of writing narrative non-fiction, by Matthew Ricketson. Sydney: Allen & Unwin, 2014. 282pp. ISBN 978-1-742379-35-7